Beyond the Incident: Institutional Predictors of Student Collective Action. (4th March 2018) - Baker, Dominique J.; Blissett, Richard S. L.
ABSTRACT: Since the original unveiling of the I, Too, Am Harvard campaign, which highlighted students' experiences with racially based microaggressions on Harvard's campus, more than 40 other student-led initiatives have developed their own similar campaigns. We used data on 4-year public and private, not-for-profit institutions during a 5-year period from the Integrated Postsecondary Education Data System to investigate the institutional characteristics that predict the birth of an I, Too, Am initiative. We did not find evidence that the racial diversity of higher education institutions is predictive of their propensity to have an I, Too, Am campaign. Instead, the general states of institutions' selectivity, size, and percentage of Pell Grant recipients were more predictive. Also, while we found that the current state of institutions has some predictive power, we found less evidence of this relationship for changes in the institutional state. The data suggested that the tipping points that motivate student social movement mobilization may not be primarily related to any specific change in institutional characteristics, but rather that they existed in a context of standing institutional characteristics.